Penerapan Miranda Rule pada Para Terpida Kasus Vina Cirebon - Hamirul (Jurnal Pustaka Cendekia Hukum dan Ilmu Sosial, 2024)
The Vina murder incident that occurred in Cirebon 2016 has many issues that still leave behind several problems, including not being given access to legal aid for prisoners, in this case the application of the Miranda rule to the treatment of prisoners using a qualitative approach with descriptive methods by collecting data from various sources. both through discourse and with existing podcasts and YouTube. In the Cirebon Vina Case, the convicts did not have access to the law and the abuse and intimidation carried out against the convicts did not apply the Miranda Rule principles so that the convicts were punished based on providing information obtained through an incorrect process, in this case the torture process and the the arrest did not comply with procedures so that the arrest of the convicts should have failed by law and the convicts should have been released.